Modification of the transmission spectrum of the ”semiconductor-dielectric” photonic crystal in an external magnetic field - Eliseeva, S. V.; Fedorova, I. V.; Sementsov, D. I. (Advanced Electromagnetics, 2017)
In this paper, some features of electromagnetic transmission of the waves of ”semiconductor dielectric” periodic Bragg structure with a finite number of periods have been investigated. In the absence of absorption, for a structure with p-type semiconductor layers, we have analyzed the dependences on the external magnetic field of photon spectrum and transmission coefficient spectrum. It has been shown that with an increasing magnetic field, there is a significant narrowing of bandwidth and broadening of band gaps, as well as formation of new band gaps in the resonance region. The boundaries of all forbidden and allowed bands are shifted to higher frequencies with the increase of the angle of radiation incidence.